Improved meal presentation increases food intake and decreases readmission rate in hospitalized patients. Issue 5 (October 2016) - Navarro, Daniela Abigail; Boaz, Mona; Krause, Ilan; Elis, Avishay; Chernov, Karina; Giabra, Mursi; Levy, Miriam; Giboreau, Agnes; Kosak, Sigrid; Mouhieddine, Mohamed; Singer, Pierre
Summary: Background: Reduced food intake is a frequent problem at a hospital setting, being a cause and/or consequence of malnutrition. Food presentation can affect food intake and induce nutritional benefit. Objectives: To investigate the effect of improved meal presentation supported by gastronomy expertise on the food intake in adults hospitalized in internal medicine departments. Design: Controlled before and after study. Methods: Two hundred and six newly hospitalized patients in internal medicine departments were included and divided in two groups, a) control: receiving the standard lunch from the hospital and b) experimental: receiving a lunch improved in terms of presentation by the advices received by the Institut Paul Bocuse, Ecully, Lyon, France together with the hospital kitchen of the Beilinson Hospital, without change in the composition of the meal. The amount of food left at the participants' plates was estimated using the Digital Imaging Method, which consisted in photographing the plates immediately to previous tray collection by the researcher. In addition, the nutritionDay questionnaire was used to measure other variables concerned to their food intake during hospitalization. Charlson Comorbidity Index was calculated. Results: There was no significant difference between the groups regarding demography or Charlson Comorbidity Index. Patients who received the meal with the improved presentation showed significantly higher food intake than those who received the standard meal, despite reported loss in appetite. Participants from the experimental group left on their plate less starch (0.19 ± 0.30 vs. 0.52 + 0.41) (p < 0.05) and less from the main course than the control group (0.18 + 0.31 vs. 0.46 + 0.41) (p < 0.05). However, both of the groups left the same amount of vegetables (0.37 + 0.36 vs. 0.29 + 0.35) (p > 0.05). Both of the groups were asked how hungry they were before the meal and no significance was shown. More participants from the experimental group reported their meal to be tasty in comparison to those in the control group (49.5% vs. 33.7% p < 0.005). Length of stay was not different but readmission rate decreased significantly in the study group (p < 0.02) from 31.2% to 13.5%. Conclusion: Improvement of meal presentation at a hospital setting can increase food intake, reduce waste food substantially and reduce readmission rate to hospital.